(untitled) (Eurasian Journal of Engineering and Technology, 2022)
In this article, experiments were conducted on the practical method of revitalizing and maintaining mulberry silkworm seeds and the electro technological method. Also, by using an electro technological method for the revitalization and maintenance of mulberry silkworm seeds by saturating the air of the incubator and worm house with negative ions using an aero ionization device during the cultivation of mulberry silkworm cocoons, the process of revitalizing the mulberry silkworm seeds was shortened, the percentage of revival increased and In the process of caring for mulberry silkworms, various diseases can be prevented and thus the possibilities of increasing cocoon productivity are presented. In addition, the calculation results of the economic efficiency achieved by using a new electro technological device for the process of incubation and care of silkworms are presented